PENERAPAN LATIHAN SENAM PROLANIS DALAM MENURUNKAN KADAR GULA DARAH PASIEN DIABETES MELITUS - Eva Susanti; Sumitro Adi Putra; Jawiah Jawiah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2022)
Diabetes mellitus is a disease with metabolic disorders due to hormonal disorders that cause various chronic complications in the eyes, kidneys, and blood vessels accompanied by lesions on the basement membrane in examination with an electron microscope. (Brunner and Suddarth, 2002) Elderly includes middle age (middle age), namely the age group 45-59 years, elderly (elderly) namely the age group 60-74 years, the elderly (old) between the age group 75-90 years and very old (very old) over the age of 90 years (Nugroho, 2008 The approach method is in the form of counseling and prolanis exercise for the elderly. The results of its implementation can increase knowledge about Diabetes Mellitus and the application of prolanis exercise for the elderly with Diabetes Mellitus which is carried out regularly can help reduce blood sugar levels in the elderly so that the elderly can work independently in meeting their needs and can improve the quality of life of the elderly.